Para uma crítica da concepção de política social do Banco Mundial na cena contemporânea - Teixeira, Rafael Vieira (2009)
The present work congregates the elements that compose the conception of social politics of the World Bank from recent reports published on the subject poverty and society in the official page of this organism. The central idea is of that it is about a critical of the conception of social politics of the Bank, discussing each one of its more explicit arguments with the intention of make to mention a organicly entailed scienter to a class perspective. This perspective is present in the interests of the articulated segments of the bourgeoisie around a directed ampler society project for the capitalist reorganization in a conjuncture of structural crisis. The conception of social politics of the World Bank follows, therefore, a deeply ideological dimension and politics, relegating to a sufficiently inferior plan the paper that this type of politics must have in the conception that subsidizes the present analysis. Being expression of the contradiction of interests of antagonistic classes, the social politics assumes, in the capitalism, the character of space of dispute. It have the incumbency to evidence more and plus such contradictions and antagonisms, despite it takes care of the necessities of the segments that demand it. The use for the Bank of instruments, as the analyzed documents, to affirm the bourgeois hegemony in the scene contemporary, certify that the shock ideological politician and continues present. It shows the present time of the fight of classes. Such fact points the urgency of the organization of the diligent classes with respect to itself, that it must be mind in the search for the unit around a project that takes care of to the yearnings, collective necessities and demands. It shows to the formation necessity politics and theoretician whom the construction of this project subsidizes. It fits to remember that it are of landmarks of the capitalist social order, the social politics acquires a paper that surpasses the action condition compensatory repairmen or in face of the competition incapacities. We affirm that the social politics must have the car condition head of the social development, relegating the production and the distribution of goods and services to the attendance of the necessities of the population. This perspective is the defended one in the present work.